Dilema Religiusitas: Sebuah Paradoks Terkait Implementasi SDG - Luky Patricia Widianingsih; Riyono, Kenley Maccauley (Politeknik Piksi Ganesha Indonesia, 2024)
This study is undertaken to offer empirical insights into the impact of countries with varying levels of religiosity and different GDP conditions on the implementation of the Sustainable Development Goals (SDGs). There are 127 countries in the world as the sample. The data analysis method uses multiple regression analysis. To separate between low and high-religiosity countries, the data is separated based on the median of religiosity. The religiosity variable uses an index religiosity publication, GDP uses a measure of country income released by the World Bank, while the implementation of SDGs uses an index released by the United Nations. The results of this study show that religiosity has a negative effect on SDG while GDP has a positive effect on SDG. The findings of this study should be interpreted with caution. Commitment to realizing sustainability goals needs the support of various stakeholders, according to the findings of this research including religious leaders, government, and the community.